The influence of athletes’ gratitude on burnout: the sequential mediating roles of the coach–athlete relationship and hope - Dong, Liangshan; Zou, Shisi; Fan, Rong; Wang, Bin; Ye, Lv (Frontiers in Psychology, 2024)
Athlete burnout is a widespread psychological syndrome in competitive sports. Prior research has focused on the negative factors contributing to burnout, but the domain of positive psychology has only recently started to explore how positive affects and mental states might combat this syndrome, with limited empirical studies to date. This study explores the relationship between athlete gratitude, the coach-athlete relationship (CAR), hope, and burnout among athletes. We employed a cross-sectional design, utilizing cluster sampling to select a cohort of females) from national training teams and professional sports teams across various provinces.Participants completed self-administered questionnaires, including the Gratitude Questionnaire, CAR Questionnaire, Hope Questionnaire, and Athlete Burnout Questionnaire. Structural equation modeling was utilized to perform confirmatory factor analysis in AMOS 24.0, alongside descriptive statistics and correlation analyses using SPSS 20.0. Our findings revealed significant associations between athlete gratitude, CAR, hope, and burnout. Furthermore, gratitude directly influenced burnout and indirectly through CAR and hope, with a sequential mediation observed through CAR and hope. This study sheds light on how gratitude relates to athlete burnout and underscores the importance of positive psychological constructs in predicting burnout, offering valuable insights for prevention and intervention strategies. These results advocate for interventions that enhance gratitude among athletes, foster a positive CAR, and boost hope levels to alleviate burnout symptoms.